Analisis Pengaruh Inflasi, Suku Bunga SBI, Nilai Tukar, Produk Domestik Bruto (PDB) dan Indeks Dow Jones Industrial Average (DJIA) Terhadap Indeks Kompas100 Periode Januari 2012-Desember 2017 - DWI PUSPITA, MAYA; SENO AJI, TONY (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract This study aims to analyze the effect of Inflation, SBI rate, exchange rate, Gross Domestic Product (GDP) and Dow Jones Industrial Average (DJIA) toward Kompas100 index period January 2012-December 2017.This research uses monthly growth ratio to calculate the stock prices, Inflation, SBI rate, exchange rate, Gross Domestic Product (GDP) and DJIA.Sampling technique used is saturation sampling where all members of the population enter into the sample. The data used in this study is secondary data obtained from the official website of Bank Indonesia, Central Bureau of Statistics and Indonesia Stock Exchange. The analytical method used multiple regression analysis.The results of the research show that the exchange rate on IDR and DJIA affect toward Kompas100 index. While the inflation, SBI rate, and GDP growth do not affect toward Kompas100. Therefore, further research should examine other potential independent variables.Keywords: Kompas100, Inflation, Exchange Rate, Gross Domestic Product, Dow Jones Industrial Average